Developing STEM-based LKPD to improve student's critical thinking abilities - Korinti Nalsalisa Br Milala; Fauziyah Harahap; H. Hasruddin (Inovasi Kurikulum, 2024)
Students' critical thinking skills in science learning remain low due to suboptimal teaching approaches. This study aims to develop and assess the feasibility, practicality, and effectiveness of STEM-based student worksheets (LKPD) on the life cycle topic for fourth-grade students at SDN 064027 Karang Sari. The research employed a Research and Development (RD) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data collection methods included observations, interviews, and tests, while data analysis was conducted through expert validation, practicality tests, and effectiveness evaluations. The results showed that the STEM-based LKPD is feasible, practical for classroom implementation, and effective in enhancing students' critical thinking skills. The LKPD supports active learning and fosters 21st-century skills such as critical thinking, creativity, collaboration, and communication. The STEM approach provides meaningful learning experiences by integrating science, technology, engineering, and mathematics, enabling students to relate learning concepts to real-life contexts. This study recommends the STEM-based LKPD as an innovative alternative for science education, particularly for the life cycle topic, to enhance students' critical thinking skills and conceptual understanding.  AbstrakKemampuan berpikir kritis peserta didik dalam pembelajaran IPA masih rendah akibat pendekatan pembelajaran yang belum optimal. Penelitian ini bertujuan mengembangkan dan menguji kelayakan, kepraktisan, serta keefektifan Lembar Kerja Peserta Didik (LKPD) berbasis STEM pada materi daur hidup untuk peserta didik kelas IV di SDN 064027 Karang Sari. Penelitian menggunakan pendekatan Research and Development (RD) dengan model ADDIE yang terdiri dari tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Teknik pengumpulan data meliputi observasi, wawancara, dan tes, sedangkan analisis data dilakukan melalui validasi ahli, uji kepraktisan, dan uji keefektifan. Hasil penelitian menunjukkan bahwa LKPD berbasis STEM layak digunakan dalam pembelajaran, praktis diterapkan, dan efektif meningkatkan kemampuan berpikir kritis peserta didik. LKPD ini dirancang untuk mendukung pembelajaran aktif, berorientasi pada pengembangan keterampilan abad ke-21, seperti berpikir kritis, kreativitas, kolaborasi, dan komunikasi. Pendekatan STEM memberikan pengalaman belajar yang bermakna melalui integrasi sains, teknologi, rekayasa, dan matematika, sehingga peserta didik dapat mengaitkan konsep pembelajaran dengan kehidupan sehari-hari. Penelitian ini merekomendasikan penggunaan LKPD berbasis STEM sebagai alternatif inovatif dalam pembelajaran IPA, khususnya pada materi daur hidup, untuk membantu peserta didik meningkatkan keterampilan berpikir kritis dan pemahaman konseptual.Kata Kunci: Berpikir kritis; LKPD; STEM.